Pengaruh Penggunaan Gadget dan Game Online terhadap Interaksi Sosial Peserta Didik - Pangestu, Deviyanti; Habibi, Roy Kembar; Yulianti, Reni Dwi; Perdana, Dayu Rika (Lentera: Jurnal Ilmiah Kependidikan, 2024)
This research aims to determine the effect of using gadgets and online games on students social interactions. This type of research is quantitative with ex-post facto research methods. The sample in this research is consisted of 58 students. The sampling technique uses simple random sampling. The data analysis technique uses the simple regression test. The results of the research show that the correlation coefficient has a positive and significant influence on the use of gadgets on students social interactions with a value of 0.014 with very low criteria and the correlation coefficient has a positive and significant influence with the use of online games on students social interactions with a value of 0.001 with very low criteria. Then, the coefficient of determination (The R2) obtained was 0.448, which means that the use of gadgets and online games has had an influence of 44.80% on students social interactions and 55.20% of the relationship is influenced by other variables not researched.